Inovasi Strategi Pemasaran Pembiayaan Mas Antam Pada Produk Arrum Haji ( Studi PT Pegadaian Syari’ah Bangil – Pasuruan ): Inovasi Strategi Pemasaran Pembiayaan Mas Antam Pada Produk Arrum Haji ( Studi PT Pegadaian Syari’ah Bangil – Pasuruan ) - Azizah, Lailatul (Universitas Airlangga, 2024)
The fact is that every year the departure quota for prospective hajj pilgrims is relatively small and the waiting list is quite long, draining time, money & energy. With the high level of community need for hajj financing, Shari'a Leasing Company Bangil–Pasuruan is here. As a business opportunity/enterprise that operates in the field of hajj financing products (hajj arrum), an easy, fast, precise, and safe solution in overcoming the problem of registration needs & obtaining a hajj portion number, especially in middle to lower economic communities, just by pawning gold from antam as collateral with the financing concept: no banks, usury, fines and confiscations. Through the application of the concept of rahn, ijarah & qard contracts. From the results of field data analysis, it is clear that there are 4 forms of innovation in gold from antam financing strategy applied to arrum hajj products, name: 1. product (gold savings program with 4T concept on credit), 2. price (gold from antam guarantee 3.5 grams customers can make & get a hajj portion number, and freely choose the number of installments & period according to economic conditions. 3. promotion (product introduction carried out online & offline), 4. service (friendly, policy, practical, easy, fast and safe). To be able to anticipate business risks for customers who fail to pay pawnshops should be able to select/measure credit worthiness by applying the 5C principles.